SAT0469 Ineffective Fracture Prevention by Bisphosphonate in Patients Undergoing High Dose Glucocorticoid Therapy with A Frax Ten Year Probability Greater than 5.8%. (10th June 2014) - Kageyama, G.; Okano, T.; Yamamoto, Y.; Sugiyama, D.; Tsuji, G.; Tsuda, K.; Takahashi, S.; Nishida, M.; Akashi, K.; Nishimura, K.; Sendo, S.; Kogata, Y.; et al.
Abstract : Background: High dose glucocorticoid (GC) therapy (PSL>0.8mg/kg/day) is often provided to patients with systemic rheumatic disease. GC induced osteoporosis (GIO) is a common complication of high dose GC therapy and bisphosphonate is frequently used as a first-line prevention of GIO and fragile fractures. However, some patients are still at high risk of bone fractures despite bisphosphonate administration. The World Health Organization fracture risk assessment tool (FRAX) is used to calculate the 10-year probability of major (hip, clinical spine, humerus or wrist fracture) fractures and has been recently adopted to the treatment guidelines for GIO and for assessment of fracture risk. Drugs more effective than bisphosphonate have recently become available, but it is unclear which patients with high dose GC therapy should be given the newer drugs for GIO prevention. Objectives: To identify patients with high dose GC therapy at a high risk of developing fragility fracture despite bisphosphonate treatment. Methods: We conducted a retrospective study on systemic rheumatic disease patients who were treated with PSL>0.8mg/kg/day at Kobe University Hospital from April 1988 to March 2012. The fracture risk at the start of high dose GC therapy was assessed by FRAX. Comparison between patients who remained fracture-free for over 5 years and those who suffered fractures within 5 years despite taking bisphosphonate were focused in particular. Results: 229 (SLE 76, Vasculitis syndrome 58, PM/DM 51, AOSD 12, MCTD 7, others 25) patients were included and the mean observational period was 1819 days (95% CI 1653-1989). 57 patients (52 clinical spinal, 3 hip, 1 humerus, 1 wrist) suffered from fracture. 28 patients suffered from fracture within 5 years despite taking bisphosphonate. 94 patients were fracture-free for over 5 years with or without bisphosphonate. Receiver operating characteristic (ROC) analysis revealed that the optimal cut-off of FRAX ten year probability failing to prevent fracture over 5 years despite bisphosphonate treatment was 5.8% (Sensitivity 89.3%, Specificity 74.5%, Area under the curve 0.885). Kaplan-Meier analysis also revealed that bisphosphonate had no effect in reducing fractures in patients with FRAX5.8%. Conclusions: Bisphosphonate is ineffective for preventing fractures in high-risk patients (FRAX≥5.8%) undergoing high dose GC therapy. Thus, these patients require alternative prophylactic measures for fragility fractures. Acknowledgements: This work was supported by the Japan Society for the Promotion of Science (JSPS) KAKENHI grants 13390768 and Japan Osteoporosis Foundation grants. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1344